The system above has 1 solution. Why you may ask... here are the steps! 2x + 5y = 10 2x + 3y = 6 2x + 3y = 6 2x + 3(2) = 6 2x + 6 = 6 2x + 5y = 10 2x = 0 -2x - 3y = -6 x=0 2y = 4 y = 2 There you go! Please vote me for Brainliest if there is a second answer!
So we can use elimination and distribute a negative one to all the terms of the second equation, so we would have -1(2x + 3y = 6). This equals -2x -3y = -6. Now subtract this from the first equation and you have 2y = 4. So y = 2. Now when plugging in 2 for y, we can wee that x must equal 0, because 2x + 5(2) = 10, means that 0 + 10 = 10, and the only way for 2x to equal 0 would be if x equals 0. The same way in the original second equation, if you plug in 2 for y, you have 2x + 3(2) = 6, and again 0 + 6 = 6 so x must equal 0. Therefore there is only one solution which is (0,2). Hope this helps :D. Feel free to ask me questions about my explanation, and ask more questions.